STRATEGI KOMUNIKASI PENYULUHAN GURU BIMBINGAN KONSELING DALAM MEMBANTU SISWA MENENTUKAN JURUSAN DI PERGURUAN TINGGI - Agatha Lin Natasha; Mariana Rista Ananda Siregar; Roni Jayawinangun (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
This study aims to determine the communication strategy of counseling guidance counselor (BK) teacher messages in guiding students to determine university majors in class XII students at SMAN 1 Sukaraja, what are the communication effects and what obstacles encountered by the Guidance Counseling teacher. This research uses Miles and Huberman data analyzing. The results show that the communication strategy of the counseling message give the counseling guidance teacher to help students determine university majors in class XII at SMAN 1 Sukaraja quite good in accordance with the communication strategy proposed by Hafied Cangara namely the determination of communicators, defines target and audience needs, preparation techniques message and media selection. Some of the obstacles that are no other than internal and external factors. Internal factors come from the school itself while external factors come from problems outside the school. The apprenticeship program from the school itself includes no campus surgical or carrer-B programs. External factors related from outside the school are family backgrounds that are less supportive of students in determining university majors. The community relations or public relation at school need to be made so that external factors could be stronger. More actively looking for scholarship programs, learning from the experience of seniors who have succeeded, balancing the desires of parents with personal ideals, so that such things must be able to be encouraging students.Keywords: communication strategy; counseling message; counseling guidance; students class XII.